Analysis of palmar grasp strength, manual cutaneous sensitivity and functional hand use in children and adolescents with chronic renal disease on hemodialysis - Souza, Thaís Thaler; Kummer, Arthur Melo; Simões e Silva, Ana Cristina; Cardoso, Ana Amélia; Lage, Carla Ribeiro; Van Petten, Adriana Maria Valladão Novais (Revista de Terapia Ocupacional da Universidade de São Paulo, 2020)
The Chronic Kidney Disease (CKD) in its terminal stage can cause significant damage when it occurs in childhood and adolescence. The objective of this study was to evaluate muscle strength of palmar grasp, manual cutaneous sensitivity and functional hand use in children and adolescents on hemodialysis. This is a cross-sectional, descriptive and analytical study that included 21 participants undergoing hemodialysis (11 via catheter and 10 per fistula), compared to 21 control participants matched by age and sex. The Jamar® dynamometer was administered to measure the palmar grip strength; the Semmes Weinstein® monofilament for cutaneous sensitivity, and the Jebsen-Taylor test for the functional use of the hands. The functional use of the hands was more compromised in the hemodialysis group in relation to the control (dominant hand p = <0.001, non-dominant p = 0.001). Palmar grasp strength was lower in the hemodialysis group compared to the control (p = <0.001) and the sensitivity suffered changes only in the fistula group because of possible damages to the median nerve (p = 0.001). Children and adolescents with CKD may present important changes in palmar grasp strength, functional use of hands and sensitivity. These results can substantiate multidisciplinary actions with this population.